Internet Access Standards: Dissemination of the Integrated Services Digital Network in Spain, 1984-2005 - Calvo, Angel (Journal of Evolutionary Studies in Business, 2021)
Abstract: This article aims to narrate the birth and evolution of the Integrated Services Digital Network (ISDN) in Spain with an essentially descriptive methodology, from an interdisciplinary perspective and from varied sources. The study aims to investigate the forms of the transition from a conceptual or engineering phase to the market in a standard of Internet access and, at the same time, in the different patterns of technological innovation and the factors that motivate them. It tries to verify if the own nature of the techniques, the degree of diffusion of the previous technologies, the technological level -digitalization- and the structure of market of the telecommunications — continued existence of the monopoly of the historical operator National Telephone Company of Spain — had a significant impact on the inequality of penetration with respect to other countries. The research authorizes to conclude that a very heterogeneous combination of factors caused that leading countries in the diffusion of a technology did not achieve that leading role in the diffusion of other technologies.
Code: Journal of Evolutionary Studies in Business Number: 2
Keywords: Business history in the Iberian Peninsula